DIGITAL PAYMENT IN RURAL REGION IN INDIA - ROOP RAJ (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In a fastest “moving digital world there is one largest growing mode of making payments called as Digital Payments. Digital payment is an emerging concept of that involves a monetary transaction between two or more people by adopting online or digital platform instead of having exchanging money physically. It is a platform where no physical interaction is required to pay or receive sum of money that can be done via mobile or computer across globe round the clock. The main objective of making payments digital is to have fair recording of all monetary transactions and safeguarding public from loos of theft of their hard earned money. COVID-19 or Coronavirus is a serious health disease due to which the whole globe was declared as pandemic and shuts all business through implementing worldwide lockdown by governments of every nation in order to safeguard health’s and lives of common people suffering to which numerous individuals lost their existence. The aim of present research is to study the concept of digital payment along with impact of COVID-19 on digital payment services especially at root level that is in towns and villages of India. The secondary research covers some view-points or insights of other researches who contributed their knowledge in related concern. The conclusion of present research paper shows that there is an high increase in use of digital payments services through various applications in Indian towns and villages which was not much high” before the happening of world-wide pandemic Covid-19.